2019
DOI: 10.21307/jofnem-2019-020
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Pepper Carrying N, Me1, and Me3 have Different Effects on Penetration and Reproduction of Four Major Meloidogyne species

Abstract: Root-knot nematode (Meloidogyne spp.) exhibits a substantial problem in pepper production, causing reduction in yield throughout the world. Continued assessment for root-knot resistance is important for developing new resistance cultivars. In this study, the effect of Me and N genes on the penetration and reproduction of M. incognita race 3, M. arenaria race 1, M. javanica, and M. haplanaria was examined under controlled greenhouse conditions using susceptible and resistant pepper lines/cultivars (Mellow Star,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…Least-squares means (LS-means) t-tests demonstrating if the mean was significantly different from 0 were used to determine whether the nematode Rf was different from 1 (the base 10 algorithm of 1 is 0). Therefore, single t-tests that showed the treatment mean was significantly different from 0 indicated that the Rf deviated significantly from 1 (Hajihassani et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Least-squares means (LS-means) t-tests demonstrating if the mean was significantly different from 0 were used to determine whether the nematode Rf was different from 1 (the base 10 algorithm of 1 is 0). Therefore, single t-tests that showed the treatment mean was significantly different from 0 indicated that the Rf deviated significantly from 1 (Hajihassani et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Management of plant-parasitic nematodes in vegetable plasticulture or bare-ground systems in the southern US relies heavily on pre-plant fumigation of soil with 1,3-dichloropropene (Telone II), Chloropicrin or metam sodium (Vapam), followed by in-season application of non-fumigant nematicides (Hajihassani, Davis, and Timper, 2019). One of the alternative management methods is the use of nematodesuppressive cover/trap crops to reduce nematode populations in soil.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations